Qualidade dos frutos de maná-cubiu minimamente processados submetidos a dois tipos de corte e diferentes concentrações de ácido ascórbico - Fujita, Érika [UNESP]; Vieites, Rogério Lopes [UNESP]; Daiuto, Érica Regina [UNESP] (My University, 2013)
The aim of this study was to evaluate the quality of the fruits of fresh cut manna-cubíu,in differentconcentrations of ascorbic acid under refrigerated storage. The sliced fruits and cut in four parts they wereimmersed in solution of ascorbic acid in the concentrations of 0%, 1%, 2% and 3%. After immersion in the solution the fresh cut fruit were drained, conditioned in trays of expanded polystyrene (EPS), covered by plastic film of polyethylene of low density (PEBD) and stored under refrigeration to 6ºC for 10 days. Every two days, the pH, soluble solids (SS) content, tritable (TA) acidity and weight loss were evaluated. There was influence of the cut type on the quality of the fresh cut mana-cúbiu. The pieces samples presented better visual aspect and smaller mass loss in relation to the sliced samples. The appraised parameters didn't show effect expressive of the different concentrations of ascorbic acid in the conservation of the fresh cut mana-cúbiu.

O objetivo deste trabalho foi avaliar a qualidade dos frutos de maná-cubíu, minimamente processados, emdiferentes concentrações de ácido ascórbico sob armazenamento refrigerado. Os frutos fatiados e cortados emquatro partes foram imersos em solução de ácido ascórbico nas concentrações de 0%, 1%, 2% e 3%. Apósimersão na solução os frutos minimamente processados foram drenados, acondicionados em bandejas depoliestireno expandido (EPS), revestidas por filme plástico de polietileno de baixa densidade (PEBD) earmazenados sob refrigeração a 6ºC por 10 dias. A cada dois dias, avaliou-se o pH, teor de sólidos solúveis eacidez titulável. Houve influência do tipo de corte sobre a qualidade do maná-cúbiu minimamente processado.As amostras em pedaços apresentaram melhor aspecto visual e menor perda de massa em relação às amostrasfatiadas. Os parâmetros avaliados não mostraram efeito expressivo das diferentes concentrações de ácidoascórbico na conservação do maná-cúbiu MP.
Fresh cut mana-cubiu quality submitted to two types of cut and different concentrations of ascorbic acid
Keywords: Solanum sessiflorum Dunal; Ascorbic acid; Processing; Solanum sessiflorum Dunal; Ácido ascórbico; Processamento